2013
DOI: 10.1155/2013/687069
|View full text |Cite
|
Sign up to set email alerts
|

Pathobiology of Obstructive Sleep Apnea-Related Dyslipidemia: Focus on the Liver

Abstract: Obstructive sleep apnea and dyslipidemia are common medical disorders that independently increase vascular morbidity and mortality. Current animal and human data show that, indeed, obstructive sleep apnea may mediate pathological alterations in cholesterol and triglyceride metabolism. The mechanisms involved are increased lipolysis, decreased lipoprotein clearance, and enhanced lipid output from the liver. Human evidence shows that the treatment of obstructive sleep apnea with continuous positive airway pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

2014
2014
2019
2019

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(13 citation statements)
references
References 46 publications
1
12
0
Order By: Relevance
“…Functional enrichment analysis suggested that most of these genes are directly involved in the above-mentioned biological processes ( Figure 2 ), which are highly relevant for OSA. Several pathways found in our study have already been discussed by many authors with inconclusive evidence [ 26 – 33 ] before as well as their involvement in the pathogenesis of OSA. For instance, Diefenbach et al [ 34 ] showed the positive association between EDN1 variant Lys198Asn genotype and OSA.…”
Section: Discussionsupporting
confidence: 50%
“…Functional enrichment analysis suggested that most of these genes are directly involved in the above-mentioned biological processes ( Figure 2 ), which are highly relevant for OSA. Several pathways found in our study have already been discussed by many authors with inconclusive evidence [ 26 – 33 ] before as well as their involvement in the pathogenesis of OSA. For instance, Diefenbach et al [ 34 ] showed the positive association between EDN1 variant Lys198Asn genotype and OSA.…”
Section: Discussionsupporting
confidence: 50%
“…13,15 Obstructive sleep apnea causes hyperlipidemia by increasing lipid synthesis and decreasing clearance of lipopro-teins. 34 An earlier report suggested a close association between OSA and cardiovascular disease. 44 Research evidence has also suggested that OSA increases the incidence of stroke.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism for the impact of IH on lipids may be due to the IH-mediated increases in gene expression of the hypoxia inducible factor family, generation of reactive oxygen species, stearoyl-coenzyme A desaturase-1, altered lipid peroxidation, and sympathetic system dysfunction 379,380. Catecholamines, whose levels are elevated in OSA, modulate the activity of adipocyte hormone-sensitive lipase via their counter-regulatory effects of antagonizing insulin, leading to the lipolysis and consequent breakdown of triglycerides into free fatty acids (FFA) and glycerol, which then will be resynthesized in the liver to form very low density lipoprotein (VLDL) 381. Supporting this putative mechanism, adults with OSA have elevated levels of FFA;382 these nocturnal surges in hepatic FFA production in adults with OSA may accelerate CVD progression and concomitant cardiac dysfunction 383.…”
Section: Obstructive Sleep Apnea and Cardiometabolic Riskmentioning
confidence: 99%